Problem Objektifikasi Wanita di Media Sosial: Tinjauan Kritis Konsep Gender : The Problem of Objectification of Women in Social Media: A Critical Review of the Concept of Gender - Maryam, Anisah; Fazira Siregar, Era; Armiya; Taufiq, Muhammad (Center of Islamic and Occidental Studies, 2024)
The objectification of women on social media is an increasingly alarming phenomenon in the digital age. Content that is widespread through various platforms often positions women as sexual objects who are judged based on physical appearance alone. This research aims to critically examine the problem of objectification of women in social media through the perspective of the concept of gender. By using the approach of feminist theory and gender analysis along with criticism of it. This research explores how misconceptions of patriarchal culture, gender stereotypes, and the capitalization of women's bodies play an important role in the reproduction and normalization of this objectification and how Islam views it. In order to understand and offer solutions to this phenomenon, the research also highlights the importance of a balanced view of the problem and the need to reflect on evidence of alternative solutions alongside the echoes of the globalized feminist narrative. The results of the research are expected to contribute to the provision of new insights in understanding the dynamics of women's objectivity and the ethical and fair use of social media.